A Study of Consecutive Terrestrial Gamma‐ray Flashes Using the Gamma‐ray Burst Monitor. Issue 11 (8th November 2018) - Stanbro, M.; Briggs, M. S.; Roberts, O. J.; Cramer, E. S.; Cummer, S. A.; Grove, J. E.
Abstract: The Fermi Gamma‐ray Burst Monitor (GBM) has detected terrestrial gamma‐ray flash (TGF) pulses and TGF pairs with separations from submilliseconds to several minutes. Enhancements in the TGF rate are reobserved on successive orbits. We report on the distribution of TGF pulse separations observed with Fermi GBM. Additionally, a detailed analysis is performed on TGFs that have temporal associations within 3.5 ms with radio atmospheric signals (sferics) from the World Wide Lightning Location Network or the Earth Networks Total Lightning Network. Sferics are typically associated with lightning discharges, but the relativistic runaway electron avalanche process, according to models, should also produce radio emissions. The separations times between TGFs show a gap from 10 ms to 1 s that we interpret as showing differing origins for the separations below 10 ms and those above 1 s. Analysis of paired TGFs with separation time ≥1 s reveals 51 pairs with a sferic association with both members. The majority of these pairs have members originating from separate cells in thunderstorm systems, but 10 pairs have geolocations consistent with originating from the same cell. The minimum separation time of pairs from the same cell is 10 s, with an average separation time of 56 s. This leads to implications on TGF generation models and the recharge time of the large‐scale electric field at the source of the production of the TGF. This separation time would result in a constraint on the recharge time of the large‐scale electric field before an additional TGF can be produced. Key Points: A gap in separation time of TGF emissions distinguishes two differing origins Ten TGF pairs have origins consistent with the same thunderstorm cell The minimum separation time between multiple TGFs from the same cell is 10 s